Industry 4.0: Multi-output regression for automatization of the USW machines welding validation process - Pimenta, João Carlos Vicente Colaço de Abreu (2022)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science